PENGARUH LATIHAN REACTIVE BOX JUMP TERHADAP HASIL LOMPAT JAUH MAHASISWI PENJASKESREK 5A TAHUN AJARAN 2015/2016 - Zamri Zamri; Ramadi Ramadi; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The purpose of this research is to know the effect of reactive box jump training on the results of long jump female students 5A academic year 2015/2016. The population in this research is 9 people. This research technique using total sampling technique. The instrument used is the long jump result. Based on research conducted on 9 sample people by doing preetes (preliminary test) of long jump result. Then continued with Reactive box jump for 16 meetings, after that done postes long jump results, results obtained from pretest and postes in t-test analyzes. The result of hypothesis test shows that the tcount of 3,784 with ttable 1,860 mean thitung>ttable, then H_a accepted, at alfa (α) 0,05. Based on the analysis and statistics,there is an average preetest of 2,78 and average posttest 2,99 with a difference of average value is 21. It can be concluded that there is an effect of reactive box jump training on the long jump results of female students in the 5A academic year 2015/2016.Keywords : Reactive box jump,long jump